PELATIHAN DAN PENDAMPINGAN KADER POSPAUD DALAM PENGELOLAAN MODEL PEMBELAJARAN YANG AKTIF DAN KREATIF - Hasrul Hasrul; Wasliaty Sirajuddin; Aslinda Hafid (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community partnership program is “Training and Assisting POSPAUD Cadres in the Management of Active and Creative Learning Models”. This program aims to improve the knowledge and skills of cadres in managing active and creative learning models such as planning learning activities and learning materials that are appropriate to the developmental stages of children by utilizing educational game tools (APE). so that it will have an impact on the quality of learning in POSPAUD. This PKM was carried out at the POSPAUD "PKBM Amanat Rakyat" the reason for choosing this POSPAUD because of the team's initial observation PKM ITKeS Muhammadiyah Sidrap see the learning process does not apply active and creative learning besides that the cadres have never attended training related to their work. The method used in this PKM activity is Participatory Rural Appraisal (PRA). In detail, to achieve the objectives of one of these programs, the activities carried out are: increasing knowledge of PosPAUD cadres in the management of active and creative learning, complete the facilities and infrastructure, socialization, and promotion to parents of toddlers. The results of this activity are: (1) there was an increase in the knowledge of cadres as much as 87% (Good), (2) PosPAUD work program continues (3) Procurement of facilities and infrastructure (APE) indoor and outdoor (4) give continuous assistance at PosPAUD "PKBM Amanat Rakyat" (5) PostPAUD service promotion